Nature, culture, imperialism - Arnold, David (ed.) (Delhi, 1995)
Environmental history, the study of changing human relations with the natural world, is a fast developing field of historical enquiry. In both ecological and cultural terms, South Asia is characterized by an unparalleled diversity. It thus offers unique possibilities for the environmental historian. Ecological degradation, and the social conflicts that have come in its wake, have further underlined the need for historical research in this field. This volume brings together a set of pioneer ing essays in the environmental history of South Asia. The contributors come from Australia, Britain, France, India and the United States: they include some of the best known historians of the subcontinent. Forests and water, the two natural resources perhaps most critical to the economic life of agrarian communities, loom large in many of the essays. Other contributions deal with pastoralists and fisherfolk, two important social groups neglected by historians; and with urban pollution, an environmental problem of enormous magnitude that has rather longer roots than is sometimes imag ined. Some essays document the radical reshaping of resource use patterns under colonial rule; others focus on the environ ment as a contested space, the site of conflict and confrontation.
Keywords: Environment-South Asia-history-1600-1922